Job strain and risk of obesity: systematic review and meta-analysis of cohort studies - Kivimäki, M (Int J Obes (Lond), 2015)
Job strain, the most widely used indicator of work stress, is a risk factor for obesity-related disorders such as cardiovascular disease and type 2 diabetes. However, the extent to which job strain is related to the development of obesity itself has not been systematically evaluated. We carried out a systematic review (PubMed and Embase until May 2014) and meta-analysis of cohort studies to address this issue. Eight studies that fulfilled inclusion criteria showed no overall association between job strain and the risk of weight gain (pooled odds ratio for job strain compared with no job strain 1.04, 95% confidence interval (CI) 0.99–1.09, N(Total)=18 240) or becoming obese (1.00, 95% CI 0.89–1.13, N(Total)=42 222). In addition, a reduction in job strain over time was not associated with lower obesity risk (1.13, 95% CI 0.90–1.41, N(Total)=6507). These longitudinal findings do not support the hypothesis that job strain is an important risk factor for obesity or a promising target for obesity prevention.